Genesis of late cretaceous intra-oceanic arc intrusions in the Pertek area of Tunceli province, eastern Turkey, and implications for the geodynamic evolution of the southern Neo-Tethys: Results of zircon U–Pb geochronology and geochemical and Sr–Nd isotopic analyses - Sar, Abdullah; Ertürk, Mehmet Ali; Rizeli, Mustafa Eren (My University, 2019)
The plutonic units of the Elazığ magmatic complex crop out in the Pertek area of Tunceli Province (eastern Turkey) in the Southeast Anatolian Orogenic Belt (SAOB). Three stages of plutonic activity can be recognised on the basis of order of formation and geochemistry: (1) a first stage of gabbro, diorite, tonalite and quartz diorite; (2) a second stage of granite, granodiorite and quartz monzodiorite; and (3) a third stage of quartz monzonite and monzodiorite. Geochemical analyses show that the intrusive rocks are metaluminous I-types that vary in composition from tholeiitic to shoshonitic. The first- and second-stage intrusive rocks formed in an intra-oceanic arc setting, and the third-stage shoshonitic intrusive rocks formed in a collision setting. In this paper, we present the results of zircon U–Pb dating and geochemical and Sr–Nd isotopic analyses. The zircon U–Pb dating indicates emplacement of these rocks between 80.6?±?0.9 and 77.2?±?1.1?Ma (Late Cretaceous). Primitive mantle-normalised trace element concentrations show enrichments in large ion lithophile elements (LILEs) and light rare earth elements (LREEs). The values of 87Sr/86Sr(i) range from 0.70575 to 0.70748, 143Nd/144Nd(i) from 0.512453 to 0.512876, and ?Nd(i) from ?1.7 to +6.7. Our results shed new light on the possible sources and evolution of the magmas during the northward subduction of the oceanic plate of the southern branch of the Neo-Tethys during the Late Cretaceous.
Makale - Bilimsel Dergi Makalesi - Çok Yazarlı
Keywords: Intra-oceanic arc; Sr–Nd isotope; U–Pb dating; Late Cretaceous magmatism; Eastern Turkey